The importance of grammar in SMA English textbooks in Indonesia to promote students’ linguistic competence - Sukur, Silvester Goridus (Journal of English Language and Pedagogy, 2021)
This research aims to analyze how far the English textbooks that were written based on the 2013 Curriculum for Senior High School (SMA) learners in Indonesia have developed grammar-related material for students to improve their grammatical competence for their needs in English communication. This research is a qualitative content analysis of the English textbooks for SMA students conducted in Yogyakarta Special Territory from July to December 2020. The data for this research were gathered from three English textbooks for SMA students: Bahasa Inggris X, Bahasa Ingris XI, and Bahasa Inggris XII. These three books were provided by the Government of Indonesia for SMA learners in Indonesia. The data obtained from these data sources were processed with NVivo R1 Software before being further analysed. Kappa Statistics reliability test was employed for the data reliability agreement level with the result of >0.75, categorized as excellent. The findings of this research reveal that the three selected English textbooks were not well developed in terms of grammar-oriented materials to promote their linguistic competence as one of the components in developing their English communicative competence. It is suggested that the grammatical-competence materials in the three textbooks are provided in a balanced way.